The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/cam4.188
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fluorescent profiling ofVEGFRs reveals tumor cell and endothelial cell heterogeneity in breast cancer xenografts

Abstract: Plasma membrane-localized vascular endothelial growth factor receptors (VEGFR) play a critical role in transducing VEGF signaling toward pro and antiangiogenic outcomes and quantitative characterization of these receptors is critical toward identifying biomarkers for antiangiogenic therapies, understanding mechanisms of action of antiangiogenic drugs, and advancing predictive computational models. While in vitro analysis of cell surface-VEGFRs has been performed, little is known about the levels of cell surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 110 publications
1
63
0
Order By: Relevance
“…The tumor size and VEGFR1/2 surface levels on tumor cells and tumor endothelial cells (tEC) were obtained from mouse xenografts [13]. It is observed that receptor distributions on the tumor cells and tEC exhibited multiple distributions.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor size and VEGFR1/2 surface levels on tumor cells and tumor endothelial cells (tEC) were obtained from mouse xenografts [13]. It is observed that receptor distributions on the tumor cells and tEC exhibited multiple distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Computational models can predict the dynamics of free and bound VEGF in vivo, but the current models assume that the number of cell surface receptors remains constant;2428 thus, the models are limited in their predictions of antiangiogenic therapy. Previous studies have been effective at measuring the numbers of VEGFRs in vitro29 and in vivo 30,31. Although the changes in VEGFRs have been investigated under ischemia,32 to our knowledge, the changes in surface receptors after antiangiogenic treatment have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Quantitative measurements also show the cell-to-cell variations in the density of VEGF receptors across different cell lines. 24,25 This heterogeneity is thought to influence prognosis and response to treatment, which has been observed in various experimental settings. The VEGFR2 heterogeneity was proved to influence the response to anti-angiogenic cyclophosphamide treatment in a pre-clinical model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed experimentally that tissue samples from patients with different types of cancer and different samples from patients with the same type of cancer have different receptor expressions. [24][25][26][27] Additionally, the VEGFR2 heterogeneity was shown to affect the response to an anti-angiogenic cyclophosphamide treatment in an in vitro experimental setting. 28 The patient-to-patient VEGFR1 and neuropilin variability has been associated with the response to bevacizumab treatment as intra-tumoral biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation